STRATEGY OF FARMER WOMEN GROUP THROUGH OPTIMIZATION OF EMPTY LAND UTILIZATION WITH PLANTING SEEDS IN PIPITAN VILLAGE, SERANG CITY - Rika Kartika; Nani Rohaeni; Miftahudin Miftahudin; Ine Aprianti; Tri Indriyani (Yayasan Education and Social Center, 2021)
The condition in Pipitan Village, which is the focus of this activity, is the Farmer Women Group